OBESITAS DAN RIWAYAT PENGGUNAAN KONTRASEPSI BERHUBUNGAN DENGAN KEJADIAN KANKER ENDOMETRIUM DI RSUD ABDOEL WAHAB SJAHRANIE SAMARINDA : OBESITY AND HISTORY OF CONTRACEPTION USE ARE ASSOCIATED WITH THE INCIDENCE OF ENDOMETRIAL CANCER AT ABDOEL WAHAB SJAHRANIE HOSPITAL, SAMARINDA - Nanda, A. Luthfiah; Hasanah, Nurul; Saputra Achmad, Andika Adi (Jurnal Medika : Karya Ilmiah Kesehatan, 2025)
Endometrial cancer is a malignant tumor that develops in the deepest layer of the epithelium of the uterus. Endometrial cancer is the sixth most common malignancy in women globally. Endometrial cancer incidence is influenced by a multitude of factors, including both risk and preventive factors. This study seeks to establish the correlation between obesity and a history of contraceptive use with the occurrence of endometrial cancer at Abdoel Wahab Sjahranie Regional Public Hospital Samarinda from 2020 to 2022. The study employed a case-control research design. The study population is categorized into two distinct groups, cases and controls. The study employed a total sampling technique for the case group and a purposive sampling technique for the control group. The study utilized a total of 72 data points, comprising of 36 case groups and 36 control groups that were matched according to age. The bivariate analysis employing the chi-square test yielded significant hypothesis testing results for the variables of obesity (p=0.002) and history of contraceptive usage (p=0.000). The study concludes that there is a correlation between obesity and a history of contraceptive use and the occurrence of endometrial cancer at Abdoel Wahab Sjahranie Regional Public Hospital Samarinda